Taxonomic review of the species of Neocorynura (Hymenoptera: Halictidae: Augochlorini) inhabiting Argentina and Paraguay - Smith-Pardo, Allan H. (Zootaxa, 2010)
A review of the species of the bee genus Neocorynura occurring in Argentina and Paraguay is provided. Four new species are described: Neocorynura tangophyla, Neocorynura gaucha, Neocorynura guarani, and Neocorynura sophia. The name Neocorynura pseudobaccha (Cockerell) is resurrected, it had previously been synonymized under Neocorynura jucunda (Smith). In total, eight species are known to occur in these two countries. Even though six additional species of Neocorynura have been considered to also be distributed in Argentina and Paraguay, their dubious occurrence in these countries may be due to imprecise information in the primary references or to collection data (specimen’s deposition). No specimens of such species were available in any of the collections consulted for this taxonomic study. Comments on the systematics and biogeography (including new distribution records), as well as species identification keys, are presented.